Effect of nursing workplace empowering model on quality of nursing work life as perceived by professional nurses in a governmental hospital, Cambodia - Koy, Virya; Boonyanurak, Puangrat; Chaiphibalsarisdi, Puangtip (International Journal of Research in Medical Sciences, 2017)
Background: Nursing is experiencing an unprecedented shortage of skilled professionals as supply dwindles and demand escalates. For this reason, organizations are diligently trying to understand both what attracts nurses to a certain employer and what retains nurses in an organization. The purposes of this quasi-experimental design were to study the perceptive level of professional nurses and compare the pretest and posttest the use of nursing workplace empowering model on quality of nursing work life. Methods: The Quality of Nursing Work Life Scale was used with total reliability coefficient at  = 0.843. Regarding to the study's model, the professional nurses of experimental group have been used for daily work. The Mann-Whitney tested for comparing the experimental group and control group. Moreover, the Wilcoxon Signed-Rank Test was used to compare the experimental group and control group and before and after implementing the nursing workplace empowering model. Results: The major findings indicated that the professional nurses who used NWEM were significantly higher scores than who did not use the NWEM at .05 level. In addition, the experimental group after implemented the NWEM was higher scores than before implementing NWEM at 0.05 level. Conclusions: The nurses' perceptions of structural and psychological empowerment are significantly increased flexibility, relaxation, free expression, and support. The structural and psychological empowerment had a direct effect on the all variables of the model.